2002
DOI: 10.1074/jbc.m207573200
|View full text |Cite
|
Sign up to set email alerts
|

ERK5 MAPK Regulates Embryonic Angiogenesis and Acts as a Hypoxia-sensitive Repressor of Vascular Endothelial Growth Factor Expression

Abstract: During angiogenesis, endothelial cells undergo proliferation, reorganization, and stabilization to establish a mature vascular network. This process is critical for establishing a functional circulatory system during development and contributes to the pathological process of tumor growth. Here we report that embryos deficient for the ERK5 MAPK die between embryonic days 10.5 and 11.5 with angiogenic failure and cardiovascular defects. We show that ERK5 deficiency leads to an increased expression of the vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
164
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 53 publications
7
164
0
2
Order By: Relevance
“…Targetted inactivation of either JNK1 nor JNK2 does not impact embryonic vascularization but instead causes defects in T-cell development (Dong et al, 1998;Yang et al, 1998). ERK5 knockouts die at E10-E11 not because of an inability to form primary vasculature but because of an inability to remodel that vasculature to form embryonic blood vessels (Regan et al, 2002;Sohn et al, 2002). Notably, ERK5 deficiency is accompanied by increased expression of VEGF (Sohn et al, 2002), indicating that ERK5 can regulate expression of angiogenic factors during development.…”
Section: Mkk Signaling and Blood Vessel Development During Early Embrmentioning
confidence: 99%
See 1 more Smart Citation
“…Targetted inactivation of either JNK1 nor JNK2 does not impact embryonic vascularization but instead causes defects in T-cell development (Dong et al, 1998;Yang et al, 1998). ERK5 knockouts die at E10-E11 not because of an inability to form primary vasculature but because of an inability to remodel that vasculature to form embryonic blood vessels (Regan et al, 2002;Sohn et al, 2002). Notably, ERK5 deficiency is accompanied by increased expression of VEGF (Sohn et al, 2002), indicating that ERK5 can regulate expression of angiogenic factors during development.…”
Section: Mkk Signaling and Blood Vessel Development During Early Embrmentioning
confidence: 99%
“…ERK5 knockouts die at E10-E11 not because of an inability to form primary vasculature but because of an inability to remodel that vasculature to form embryonic blood vessels (Regan et al, 2002;Sohn et al, 2002). Notably, ERK5 deficiency is accompanied by increased expression of VEGF (Sohn et al, 2002), indicating that ERK5 can regulate expression of angiogenic factors during development. In addition to its role in blood vessel formation during development, ERK5 also plays an important role in maintaining endothelial function and vascular integrity in adults since its conditional inactivation causes increased vascular permeability and hemorrhage in multiple organs (Hayashi et al, 2004).…”
Section: Mkk Signaling and Blood Vessel Development During Early Embrmentioning
confidence: 99%
“…In addition, deletion of exon 4 would result in a frame shift mutation between exons 3 and 5, preventing the correct translation of the rest of the C-terminal domain. Conditional deletion of this allele using a Mox2-CRE [43] which deletes in embryonic, but not in extra-embryonic tissues resulted in embryonic lethality between E10 and E12 (data not shown), with a similar phenotype to that described for constitutive ERK5 knockouts [20][21][22] demonstrates that lethality resulting from ERK5 knockouts cannot be rescued by restoring normal placental function, and is in agreement with the results reported for endothelial cellspecific deletion of ERK5 in the embryo [23].To analyse the role of ERK5 in T-cell development, the floxed ERK5 mice were crossed onto mice bearing a CD4-CRE transgene. T cells undergo a series of developmental stages in the thymus, which can be defined by the expression of cell surface markers.…”
mentioning
confidence: 93%
“…ERK5 has been shown to promote both the proliferation and survival of several cell lines [10,19]. Knockout mice for ERK5 die midway through gestation due to defects in the vasculature of both the embryo and placenta [20][21][22]. Inducible deletion of ERK5 in adult mice also results in death, which correlates with disintegration of the blood vessels.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of several transcriptional factors has been shown to be regulated by ERK5, including MEF2, c-Fos and Fra-1, Sap-1, c-Myc and nuclear factor-kB (Kato et al, 1997;English et al, 1998;Kamakura et al, 1999;Chiariello et al, 2000;Terasawa et al, 2003). It plays a key role in embryogenesis: ERK5 knockout mice embryos die between day 9.5 and 11.5 due to severe cardiovascular defects (Regan et al, 2002;Sohn et al, 2002) whereas mice lacking ERK1 develop normally (Pages et al, 1999;Selcher et al, 2001). A recent study has shown that MEK5 knockout mice also die, at approximately embryonic day 10.5 (Wang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%